Activation of the alternative complement pathway predicts renal outcome in patients with lupus nephritis. (July 2020) - Kim, Hyunwoo; Kim, Taehee; Kim, Miyeon; Lee, Hwa Young; Kim, Yunmi; Kang, Mi Seon; Kim, Jinseok
Objectives: The aims of this study were to clarify the activation of complement pathways in patients with lupus nephritis (LN), and to elucidate the association between these complement activation types and clinical outcomes. Methods: We enrolled 115 patients with biopsy-proven LN from 2003 to 2016 from the lupus cohort at the Busan Paik Hospital and the Jeju National University Hospital in Korea. The patients were divided into two groups based on the patterns of glomerular complements deposits. The presence of C1q, C4 and/or C3 deposits in the glomerulus was considered evidence for the activation of the classical pathway with or without alternative pathway activation (group 1, N  = 93), and glomerular C3 deposition without C1q and C4 deposits was considered as a marker for the alternative pathway limited activation (group 2, N  = 22). The study end point was progression of kidney disease defined as a ≥50% reduction in estimated glomerular filtration rate from baseline values or advancement to end-stage renal disease. Results: The mean estimated glomerular filtration rate and median urine protein-to-creatinine ratio of the patients were 85.7 ± 32.4 mL/min/1.73 m 2 and 3.1 g/g, respectively, at the time of kidney biopsy. Forty-nine patients (43%) had nephrotic range of proteinuria. Compared to group 1 patients, those in group 2 were older, were more likely to be males and were more hypertensive. In addition, plasma C3 and C4 levels were significantly lower in group 1 patients compared to those in group 2. Moreover, anti-dsDNA concentration was significantly higher in group 1 patients compared to those in group 2. The mean follow-up time was 5.4 ± 3.4 years. The rates of response to one-year immunosuppressive treatment were poorer in group 2 patients compared to those in group 1. During the follow-up time, the progression of kidney disease was significantly higher in group 2 than in group 1 patients. Conclusion: This study showed that there was alternative complement pathway limited activation in the renal tissue in a small number of patients with LN, and these patients had worse renal outcomes compared to patients with glomerular classical complement pathway activation with or without alternative pathway activation.